langdoc/spoken-komi-corpus-vaszolyi: Spoken Komi Corpus: Erik Vászolyi - Rogier Blokland; Niko Partanen; Michael Rießler (Zenodo, 2021)
This is the first part of a digital edition of Erik Vászolyi's Komi recordings. They have been transformed into a structure where the transcriptions can be compared to the archived audio; we hope to eventually be able to also add other archived versions. This version is preliminary, and the materials will be continually updated. Our goal is to provide a transcription that is accurate with regard to the original recording, and accessible also to the Komi community. The transcription conventions thereby closely follow the principles of Zyrian Komi orthography.